Effect of listening music (Rabindra Sangeet) on autonomic dysfunction in patients with generalized anxiety disorder: A power spectral analysis of heart rate variability - Mallik, Bithi; Sultana, Shamima; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2024)
Background: Power spectral analysis of heart rate variability (HRV) is a complex method for assessing cardiac autonomic nerve function (CANF) in generalized anxiety disorder (GAD) patients which is a common mental disorder in the world. Recently, music therapy is used as an adjunct to pharmacotherapy in clinical psychiatry for GAD. Objective: To observe the effect of music therapy on CANF by power spectral analysis of HRV in GAD patients was designed. Methods: This prospective non randomized intervention study was done in 2019 on 60 newly diagnosed GAD patients aged 20- 40 years, both male and female. Among them 30 patients were under music therapy with listening of Raga Bhairabi based Rabindra sangeet for 3 months and 30 patients were without music therapy for three months. Age, sex and BMI matched healthy control were also enrolled. HRV of all GAD patients and control were recorded at baseline and after three months of follow up. HRV were recorded by Power Lab 8/35. For statistical analysis Bonferroni’s Post Hoc test and paired sample‘t’ test were done. Results: Total power, LF power, HF power, LF n.u, HF n.u and LF/HF and were significantly lower in all GAD patients compared to healthy control at baseline. After 3 months of music therapy, significant increment of Total power, HF power, HF n.u and significant decrement of LF n.u and LF/HF occurred whereas no change of these except HF n.u were noted in patients without music after 3 months. Moreover, after three months of music therapy, Total power, HF n.u, and LF/HF were almost same to control. Conclusion: So this study concluded that music therapy improve autonomic dysfunction in GAD patients and can be used as an adjunct to pharmacotherapy in clinical psychiatry for good cardiac health in GAD patients. J Bangladesh Soc Physiol 2022;17(2): 91-100